In-House Design, Manufacturing, and Testing of a 2.856 GHz Combline Microwave Cavity Filter for the Low-Level RF Systems of Linear Particle Accelerators - Giannetti, G.; Bellaveglia, M.; Gallo, A.; Maddio, S.; Mostacci, A.; Piersanti, L.; Serenellini, B.; Selleri, S.; Tocci, S. (Advanced electromagnetics, 2025)
A combline microwave cavity filter has been developed to generate the 2.856 GHz radio frequency (RF) tone to be used as the master reference of SPARC_LAB electron linac facility at the Frascati National Laboratories of the National Institute for Nuclear Physics (LNF-INFN). The filter must select the 36th harmonic from a frequency comb with a repetition frequency of 79.33MHz and reject the other harmonics. The comb is generated by the electric conversion of the laser pulse train from the oscillator of the photocathode laser. Since a filter for this very specific application is off-the-shelf, it was designed, manufactured, and tested in-house at LNF-INFN. The measured insertion loss at the center frequency is 2.2 dB, the bandwidth is 30MHz (percentage fractional bandwidth is 1.1 %). This narrow bandwidth is required to ensure effective rejection (insertion loss > 65 dB) of adjacent harmonics in the frequency comb, specifically at frequencies of 2.77633 GHz and 2.93533 GHz. The purpose of filtering is to ensure that the tone, distributed in the low-level RF system, remains clean and can be used to synchronize the most crucial machine subsystems, such as RF power units, accelerating cavities, diagnostic systems, and lasers.